Characterization of complete chloroplast genome of endemic species of Korea Peninsular, Salvia chanryoenica (Lamiaceae). Issue 2 (3rd July 2018) - Ha, Young-Ho; Choi, Kyoung Su; Choi, Kyung
Abstract: Salvia chanryoenica is an endemic species, which locates on the ridges of mountains in South Korea. In this study, we determined the complete chloroplast (cp) genome sequence of S. chanryoenica ; cp genome of S. chanryoenica is 151, 689 bp in length and consists of a large (82, 903 bp) and small (17, 634 bp) single-copy regions, separated by a pair of identical inverted repeats (25, 576 bp). This genome contains unique 79 protein-coding genes, 30 tRNA, and 4 rRNA. The gene order and organization of the S. chanryoenica are consistent with those of other Lamiaceae cp genomes. The overall GC content of the whole genome was 37.9%. Phylogenetic tree constructed based on 71 protein-coding genes demonstrated a sister relationship within genus Salvia .